Pemanfaatan Pohon Literasi Untuk Meningkatkan Kemampuan Menulis Permulaan Pada Anak Usia Dini - Suradi, Didi; Masnah, Masnah (Iftitiah: Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2025)
This study aims to determine the ability to write the beginning by using the media literacy tree in early childhood. The research method uses classroom action research. The sample used was group B students from TK Al Muslim Bekasi, totaling 21 students, consisting of 10 boys and 11 girls. Data analysis techniques were carried out by comparing the percentage of students' initial writing abilities before and after taking action. This research resulted in 60% of students improving their abilities in the first cycle, with the category starting to develop, and 81% in the second cycle, with the category developing according to expectations. Thus, the use of tree literacy can improve the ability to write early in early childhood.